A Community Development Initiative for Empowering 'Cemilarupa' MSME Business Commercialization - Wibowo, Melisa; Inayah, Mutia Risky; Santoso, Vincent Putra; Scoles, Pieter; Safriyana (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy by promoting economic equality, improving welfare, increasing foreign exchange, absorbing labor, and supporting the economy during crises, in today's digital era, platforms like e-commerce, social media, and digital marketing are essential for MSMEs, to overcome challenges such as limited capital and marketing inefficiency, expand their reach, and enhance brand awareness, ultimately contributing to economic growth. These community development activities aimed to empower MSMEs in rural areas, with a focus on supporting Cemilarupa, a local MSME, in enhancing its brand awareness and optimizing its use of digital platforms. The initiative involved a series of mentoring activities, including direct fieldwork, product photography assistance, and guidance in managing e-commerce and social media accounts. The primary goal was to help Cemilarupa improve its online presence and marketing strategies. As a result, the business experienced significant improvements in brand recognition, online marketing knowledge, market reach, and sales turnover. By effectively utilizing e-commerce and social media, the project addressed key challenges faced by MSMEs in the era of globalization and digitalization. This paper highlights the positive outcomes of the initiative for Cemilarupa’s development and provides insights into the effectiveness of community development strategies aimed at MSME empowerment.